Inventory Policy Design of FMCG Products to Minimize Total Inventory Cost Using Continuous Review (r, Q) at PT ABC - Dhea Trullyani Savitri; Femi Yulianti; Hardian Kokoh Pambudi (School of Industrial and System Engineering, Telkom University, 2022)
T ABC is a start-up company that provides an online shopping platform with a variety of daily necessities,one of products offered is Fast Moving Consumer Goods (FMCG). The main problem faced by PT ABCwas the total inventory cost that exceeded the budget by 82%. This was caused by the lack of standardinventory policy calculation. To overcome this problem, a proposed inventory policy needs to be designedto obtain the optimal value of reorder point, order quantity, and safety stock. Before designing the inventorypolicy, inventory classification was conducted using ABC analysis. Then proceed with designing inventorypolicy using the continuous review method (r, Q) to minimize total inventory cost. After that, a DecisionSupport System (DSS) was designed based on the results of the proposed inventory policy using MicrosoftExcel-VBA. This research resulted the optimal value of reorder point, order quantity, and safety stock wereobtained for 42 products in category A with diverse values. Based on the proposed inventory policy, the totalinventory cost decreased by 11% or Rp281.770.103/year from the existing total cost. Then, the DSS wassuccessfully designed to assist decision makers in implementing the proposed inventory policy. Although ithad been successfully minimized, the total cost of the proposed inventory still exceeded the budget. Thiswas because the current budget had not considered all components of inventory costs, even the budget forpurchasing costs with an order quantity of as much as the number of demands was not sufficient.